ANALISIS PERAN STAKEHOLDER DALAM PENGEMBANGAN OBJEK WISATA SERULINGMAS INTERACTIVE ZOO, KABUPATEN BANJARNEGARA - Rahmawati, Anisa; Marom, Aufarul (Journal of Public Policy and Management Review, 2025)
Serulingmas Interactive Zoo as a pillar of artificial tourism in Banjarnegara Regency not only functions as a tourist attraction but also as a wildlife conservation institution. The role of stakeholders is essential because the development of tourist attractions is a dynamic dimension that cannot be done individually. The researcher uses a qualitative descriptive method with purposive and snowball sampling to select informants. Through this research, it is hoped that an analysis can be made of the extent of the contributions and effectiveness of stakeholders in the development of tourist attractions in alignment with the Master Plan for Tourism Development of Banjarnegara Regency 2015-2030. The results show that the development of marketing, industry, and institutional aspects has been very good, but the development of tourism attractions has not been optimized, mainly due to the lack of funds for the development of infrastructure and facilities. The key stakeholder, Perumda TRMS Serulingmas, has also partnered well with the government, researchers, local residents, NGOs, the media, and tourists. However, up to this point, there has been no involvement of the private sector in the development of Serulingmas Interactive Zoo, indicating the need for a partnership network plan with the private sector. In addition, issues such as communication problems, shifts in the values and principles of management, trust, and complex regulations have been encountered in the development process, causing obstacles in capital involvement. New strategies are needed from stakeholders to accelerate the development targets of Serulingmas Interactive Zoo, especially in increasing tourist visits. Communication must be built as the key to optimizing the cooperation networks between stakeholders.